Patients with large neck diameter have a higher risk of type IA endoleaks and aneurysm rupture after standard endovascular aneurysm repair - Oliveira, Nelson F.G.; Böckler, Dittmar (Journal of vascular surgery, 2019)
Objective - Standard endovascular aneurysm repair (EVAR) is the most common treatment of abdominal aortic aneurysms (AAAs). EVAR has been increasingly used in patients with hostile neck features. This study investigated the outcomes of EVAR in patients with neck diameters ≥30 mm in the prospectively maintained Endurant Stent Graft Natural Selection Global Postmarket Registry (ENGAGE). - Methods - This is a retrospective study comparing patients with neck diameters ≥30 mm with patients with neck diameters <30 mm. The primary end point was type IA endoleak (EL1A). Secondary end points included secondary interventions to correct EL1A, aneurysm rupture, and survival. - Results - This study included 1257 patients (mean age, 73.1 years; 89.4% male) observed for a median 4.0 years (interquartile range, 2.7-4.8 years). A total of 97 (7.7%) patients had infrarenal neck diameters ≥30 mm and were compared with the remaining 1160 (92.3%) with neck diameters <30 mm. At baseline, there were no differences between groups regarding demographics and comorbidities other than cardiac disease, which was more frequent in the ≥30-mm neck diameter group (P = .037). There were no significant differences between the groups regarding neck length, angulation, thrombus, or calcification. Mean preoperative AAA diameter was 64.6 ± 11.3 mm in the ≥30-mm neck diameter group and 60.0 ± 11.6 mm in the <30-mm neck diameter group (P < .001). Stent graft oversizing was significantly less in the ≥30-mm neck diameter group (12.2% ± 8.9% vs 22.1% ± 11.9%; P <. 001). Five patients (5.2%) in the ≥30-mm neck diameter group and 30 (2.6%) with neck diameters <30 mm developed EL1A, yielding a 4-year freedom from EL1A of 92.4% vs 96.6%, respectively (P = .09). Oversizing was 21.8% ± 13.0% for patients developing EL1A and 21.3% ± 12.4% for the remaining cohort (P = .99). In adjusting for neck length, AAA diameter, and device oversizing, patients with neck diameter ≥30 mm were at greater risk for development of EL1A (hazard ratio, 3.0; 95% confidence interval, 1.0-9.3; P = .05). Secondary interventions due to EL1A did not differ between groups (P = .36). AAA rupture occurred in three patients with neck diameter ≥30 mm (3.1%) and in eight patients with neck diameter <30 mm (0.7%; hazard ratio, 5.1; 95% confidence interval, 1.4-19.2; P = .016); two cases were EL1A related in each group. At 4 years, overall survival was 61.6% for the ≥30-mm neck diameter group and 75.2% for the <30-mm neck diameter group (P = .009), which remained significant on correcting for sex and AAA diameter (P = .016). - Conclusions - In this study, patients with infrarenal neck diameter ≥30 mm had a threefold increased risk of EL1A and fivefold risk of aneurysm rupture after EVAR as well as worse overall survival. This may influence the choice of AAA repair and underlines the need for regular computed tomography-based imaging surveillance in this subset of patients. Furthermore, these results can serve as standards with which new, possibly improved technology, such as EndoAnchors (Medtronic, Santa Rosa, Calif), can be compared.